2014
DOI: 10.1182/blood.v124.21.1071.1071
|View full text |Cite
|
Sign up to set email alerts
|

CRLF2 over-Expression Is a Poor Prognostic Marker in Children with High Risk T-Cell Acute Lymphoblastic Leukemia

Abstract: Pediatric T-ALL patients have a worse outcome compared to BCP-ALL patients and they could benefit from new prognostic marker identification. Alteration of CRLF2 gene, a hallmark correlated with poor outcome in BCP-ALL, has not been reported in T-ALL.We analyzed CRLF2 expression in 212 T-ALL pediatric patients enrolled in AIEOP-BFM ALL2000 study in Italian and German centers.Seventeen out of 120 (14.2%) Italian patients presented CRLF2 mRNA expression 5 times higher than the median (CRLF2-high); they had a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…These data are in consonance with the other two previous studies which did not find association between CRLF2 overexpression with the presence of overall NOTCH1/ FBWX7 mutations. 5,6 Noteworthy, to the best of our knowledge, our study showed for the first time a significant association between ICN1 stabilization and CRLF2 overexpression in T-ALL. Indeed, deregulation of proteasome-mediated degradation of ICN1 is the most common mechanism for NOTCH pathway aberrant activation in human cancers.…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations
“…These data are in consonance with the other two previous studies which did not find association between CRLF2 overexpression with the presence of overall NOTCH1/ FBWX7 mutations. 5,6 Noteworthy, to the best of our knowledge, our study showed for the first time a significant association between ICN1 stabilization and CRLF2 overexpression in T-ALL. Indeed, deregulation of proteasome-mediated degradation of ICN1 is the most common mechanism for NOTCH pathway aberrant activation in human cancers.…”
Section: Resultsmentioning
confidence: 48%
“…However, in terms of clinical outcome, others have shown that children with CRLF2 overexpression were prednisone poor responders 6,7 and had significantly worse overall survival (OS), event-free survival, and cumulative incidence of relapse. 5 In a series of adult T-ALL, cases with CRLF2-high showed significantly poorer OS (11 vs 32 months). 7 These findings highlight the importance of identifying these patients at diagnosis for an adequate clinical management.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The expression ratio was calculated using comparative Ct analysis (2 −ΔΔCt ). As in previous studies, CRLF2 high expression was defined as an expression level 20‐fold or greater than the median expression value in pB‐ALL patients and fivefold or greater than the median expression value for T‐cell acute lymphoblastic leukemia (T‐ALL) patients as previously described …”
Section: Methodsmentioning
confidence: 99%